PENGARUH MODAL USAHA DAN LOKASI USAHA TERHADAP PENDAPATAN UMKM DI DESA TAPOS I KECAMATAN TENJOLAYA KABUPATEN BOGOR - Gunawan Marwan; Moh. Zaenal Muttaqin; Moh. Asep Zakariya Ansori (Program Studi Ekonomi Syariah, 2023)
Income can be influenced by different elements, this study uses initial capital, and business location as independent variables. This study aims to determine the impact of start-up capital and business location on income. The sample of this research is 80 respondents who are MSMEs in Tapos I Village, Tenjolaya District, Bogor Regency. Data collection techniques using a questionnaire. The analysis technique used is multiple linear regression, with income as the dependent variable and initial capital and business location as independent variables. After the classical assumption test, the results of the data are normally distributed and do not experience deviations. Judging from the results of the F test, it is found that the calculated F value is 112,344 with a significant level of F 0.000, using a significant level of 0.05 and an F table value of 3.115, then F arithmetic (112.344) > F table (3.115) or a significant F 0.000 shows in below 0.05. So it can be concluded that the two independent variables, namely initial capital and business location, both affect income. Partially, initial capital and business location have a significant effect. Of the two independent variables, the most dominant variable affecting MSME income is the initial capital variable, with a t-count value of 10,790 and a significant probability of 0.000. MSMEs are one of the backbones of the Indonesian economy that must be continuously created